2016
DOI: 10.1016/j.celrep.2016.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of WAVE Regulatory Complex Activation by a Bacterial Virulence Effector Counteracts Pathogen Phagocytosis

Abstract: SummaryTo establish pathogenicity, bacteria must evade phagocytosis directed by remodeling of the actin cytoskeleton. We show that macrophages facilitate pathogen phagocytosis through actin polymerization mediated by the WAVE regulatory complex (WRC), small GTPases Arf and Rac1, and the Arf1 activator ARNO. To establish extracellular infections, enteropathogenic (EPEC) and enterohaemorrhagic (EHEC) Escherichia coli hijack the actin cytoskeleton by injecting virulence effectors into the host cell. Here, we find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 50 publications
0
37
0
Order By: Relevance
“…Previously, a number of studies [17][18][19] have indicated the involvement of both Arf6 and Arf1 in controlling phagocytosis by regulating actin assembly. Furthermore, we have previously shown [20] that Arf1 achieves this by directly mediating WRC actin polymerization, which was crucial for the phagocytosis of pathogenic E. coli. Thus, we next examined whether the Arf6-and Rac1-dependent WRC recruitment had any effect on phagocytosis.…”
Section: Arf6 Regulates Phagocytosis In Differentiated Thp-1 Human Mamentioning
confidence: 97%
“…Previously, a number of studies [17][18][19] have indicated the involvement of both Arf6 and Arf1 in controlling phagocytosis by regulating actin assembly. Furthermore, we have previously shown [20] that Arf1 achieves this by directly mediating WRC actin polymerization, which was crucial for the phagocytosis of pathogenic E. coli. Thus, we next examined whether the Arf6-and Rac1-dependent WRC recruitment had any effect on phagocytosis.…”
Section: Arf6 Regulates Phagocytosis In Differentiated Thp-1 Human Mamentioning
confidence: 97%
“…EspG also alters paracellular permeability via modulation of tight junctions, although the mechanism of this is unclear at present (113,114). In macrophages, EspG prevents phagocytosis of attached bacteria by binding to ARF6 and ARF1, ultimately preventing the WAVE-dependent Arp2/3-mediated actin polymerisation necessary for efficient uptake of the bacteria into the macrophage (115).…”
Section: Espg Manipulates Cell-cell Contacts and The Host Cell Surfacementioning
confidence: 99%
“…44 Phagocytosis in part is driven via WRC dependent actin assembly, a process that requires cooperating Arf and Rac1 GTPases. 45 In an attempt to evade this process EPEC likely interferes with one or more of these components. The effector protein EspG, know to interact with Arf1 was thus an intriguing candidate to investigate.…”
Section: Escherichia Coli Interfere With Arf Signaling To Block Wave mentioning
confidence: 99%
“…47,48 EspG was found to incapacitate WRC activation via a dual mechanism. 45 Firstly, EspG binding to Arf1 impedes cooperation with Rac1, thereby inhibiting WRC recruitment and activation. Further investigation of the mechanism by which EspG incapacitates WRC, identified key residues in the Arf1 a¡1 helix and switch-1 domain, which might be critical for WRC activation.…”
Section: Escherichia Coli Interfere With Arf Signaling To Block Wave mentioning
confidence: 99%
See 1 more Smart Citation